1987
DOI: 10.1002/star.19870390907
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Applications of Reactive Carbohydrates Part II: Graft Polymerization of Starch and Hydrolyzed Starches with Acrylamide

Abstract: starch/garke 39 (1987) Nr. 9, S. 319-322 0 VCH Verlagagesell\chafr mhH, D-694(1 Weinheim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Hydrolyzed corn starch having 0.84 m. eq. /100 gm sample was prepared according to the method mentioned elsewhere [49].…”
Section: Acid Hydrolysis Of Native Starchmentioning
confidence: 99%
“…Hydrolyzed corn starch having 0.84 m. eq. /100 gm sample was prepared according to the method mentioned elsewhere [49].…”
Section: Acid Hydrolysis Of Native Starchmentioning
confidence: 99%
“…The U.S. Department of Agriculture showed that starch‐ graft ‐polyacrylonitrile (Sr‐ g ‐pAN) hydrolyzate exhibits super absorbing properties 4. Since then, the graft copolymerization of Sr has been studied by many workers 5–31…”
Section: Introductionmentioning
confidence: 99%